An update on the NLRP3 inflammasome and influenza: the road to redemption or perdition?. (October 2018) - Tate, Michelle D; Mansell, Ashley
Highlights: The NLRP3 inflammasome is integral to IAV disease outcome via induction of protective and detrimental inflammation. Therapeutic targeting of the inflammasome can reduce inflammation and improve disease outcome. Inflammasome activation and inflammatory 'strength' is modulated via transcriptional regulation of Signal 1. Abstract : Inflammation is an integral aspect of influenza A virus (IAV) infection. It is critical to induce an antiviral environment to reduce viral replication and dissemination, while also being essential to the development and maturation of adaptive immunity, which ultimately resolves infection. Conversely, excessive pulmonary inflammation and cellular influx are characteristic of lethal IAV infections. It has become increasingly apparent that the innate immune inflammasome complex is a crucial moderator in IAV disease pathogenesis. It is responsible for the maturation and secretion of prototypic inflammatory cytokines, Interleukin (IL)-1β and IL-18, and the induction of pyroptotic cell death. This short review will examine recent work on the regulation and targeting of the NLRP3 inflammasome as a means of intrinsic and extrinsic modulation of inflammasome-mediated inflammation. It is encouraging that recent studies suggest 'starving' the inflammasome of substrate, or directly inhibiting activity, may be the means to reducing host inflammatory responses to IAV infection and to directing a positive disease outcome.